Impact of Poverty on Parent–Child Relationships, Parental Stress, and Parenting Practices - Laurie Long Kwan Ho; William Ho Cheung Li; Ankie Tan Cheung; Yuanhui Luo; Wei Xia; Joyce Oi Kwan Chung (Frontiers in Public Health, 2022)
Objectives:To explore the impact of poverty on parent–child relationships, parental stress and parenting practices.DesignA mixed methods study.SampleFour hundred and eighty five Hong Kong Chinese parents who had children aged 3-6 years, and who were from low-income families. Eleven of these parents were randomly selected for individual semi-structured interviews.MeasurementsA sociodemographic questionnaire, the parent–child relationship score, the Parental Stress Scale and the Perceived Parental Aggression Scale.ResultsThe parents were found to have an impaired relationship with their children. The findings indicated that employment status, parental stress and harsh parenting were significantly associated with parent–child relationships. The qualitative findings revealed that parents from low-income families encountered a wide range of difficulties, which made these parents more likely to experience parental stress, thereby increasing their tendency to adopt harsh parenting practices that undermined parent–child relationships.ConclusionThis study sheds light on the associations between parent–child relationships, parental stress and parenting practices in low-income families. These findings will enhance nurses' understanding of the impact of poverty on parent–child relationships, and highlight the need for nurses to ensure that underprivileged parents and their children receive adequate primary care to prevent the development of psychological problems in this vulnerable group.